Cerebral hemodynamic effects of early blood pressure lowering after TIA and stroke in patients with carotid stenosis - Mazzucco, S; Li, L; McGurgan, IJ; Assuncao Tuna, M; Brunelli, N; Binney, LE; Rothwell, PM (SAGE Publications, 2022)
Background: Effects of early blood pressure (BP) lowering on cerebral perfusion in patients with moderate/severe occlusive carotid disease after transient ischemic attack (TIA) and non-disabling stroke are uncertain.